Flexibility Versus Fixity of Exchange Rate Regimes in Developing Countries: An Empirical Assessment of Macroeconomic Effects - Rabhi, Ayoub (Journal of Applied Business and Economics, 2022)
The process of financial integration initiated by developed countries has been accompanied by a flexible exchange rate regime which is based on market supply and demand. A regime considered as being more acceptable for developed countries in a liberal context. However, developing countries, with their own economic structures, often find it difficult to choose an optimal exchange rate regime for their economies. Although many countries are floating their exchange rate regimes, touting its superiority over other exchange rate regimes, fixed exchange rates are still a resilient regime that can economically compete with flexibility. In this context, this study being presented has taken the liberty to econometrically study through panel data, the evaluation of the macroeconomic effects of exchange rate regimes on a set of emerging and developing countries through the periods of 2000-2016.